IMF Multi-Country Report : Housing Recoveries: Cluster Report on Denmark, Ireland, Kingdom of the Netherlands-the Netherlands, and Spain. (IMF Staff Country Reports; Country Report ;, 2015)
This report examines the experiences of four European countries that have had large house-price declines in recent years. In particular, it examines the experiences of Denmark, Ireland, the Netherlands, and Spain-four countries in which the house-price cycle has been especially large and that share a similar institutional environment (a common monetary policy and the EU's institutional framework)-with a view to exploring how policies can best support economic recovery in the wake of a house-price bust. The paper draws on and synthesizes related Selected Issues papers that are being or have been drafted as part of the 2014 Article IV consultations with these countries. These countries' experiences share similarities, but also important differences. Shocks to house prices, unemployment, and bank balance sheets were most severe in Ireland and Spain, reflecting in part a higher amplitude of residential construction. However, the boom- bust cycle has, together with other shocks, left all four countries facing significant output gaps, as well as elevated levels of private-sector debt that pose headwinds for growth. Promoting recovery following a house-price bust requires a multi-pronged strategy. Large house-price busts can leave countries facing wide output gaps, a highly indebted private sector, and weaker bank balance sheets. Addressing these problems simultaneously can be challenging, as efforts often involve trade-offs (e.g., faster deleveraging can widen output gaps). A careful and multi-pronged strategy is thus required to minimize trade-offs and accelerate sustainable recovery. Important progress has been made in this regard in all four countries.